2015
DOI: 10.1089/sur.2014.072
|View full text |Cite
|
Sign up to set email alerts
|

Association between Triclosan-Coated Sutures for Abdominal Wall Closure and Incisional Surgical Site Infection after Open Surgery in Patients Presenting with Fecal Peritonitis: A Randomized Clinical Trial

Abstract: The use of triclosan-coated sutures in fecal peritonitis surgery reduces the incidence of incisional SSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…Four of these included only colorectal procedures, whereas Diener et al [35] included all types of elective procedures through a midline laparotomy. Justinger et al [36] included both elective and emergency laparotomies, whereas Ruiz-Tovar et al [37] included only cases with fecal peritonitis and Mingmalairak et al [38] studied patients undergoing open appendectomies. When evaluating PDS sutures separately, there was no effect of triclosan coating on the rate of SSI (OR 0.85; CI 0.61-1.17).…”
Section: Resultsmentioning
confidence: 99%
“…Four of these included only colorectal procedures, whereas Diener et al [35] included all types of elective procedures through a midline laparotomy. Justinger et al [36] included both elective and emergency laparotomies, whereas Ruiz-Tovar et al [37] included only cases with fecal peritonitis and Mingmalairak et al [38] studied patients undergoing open appendectomies. When evaluating PDS sutures separately, there was no effect of triclosan coating on the rate of SSI (OR 0.85; CI 0.61-1.17).…”
Section: Resultsmentioning
confidence: 99%
“…After the critical appraisal of all publications, Henriksen et al was selected as the latest meta-analysis that best matched the inclusion and exclusion criteria [28]. This meta-analysis included eight randomized trials that investigated the role of TCS in preventing SSIs in adult patients undergoing gastrointestinal surgery [20][21][22][23][24][25][26][27]. In the pooled analysis, the authors found a significant reduction of SSIs in the experimental group (SSI rate 10.1% for TCS versus 13.5% for CS; OR: 0.67; 95% CI: 0.46-0.98; p = 0.04).…”
Section: Clinical Resultsmentioning
confidence: 99%
“…The characteristics of the studies included in the Henriksen et al meta-analysis are summarized in Table 3. The heterogeneity among the RCTs was high: four trials [20,23,26,27] encompassed only elective colorectal surgery, one [21] comprised all types of elective procedures through a midline laparotomy, another [22] included both elective and emergency laparotomies, another [24] evaluated only emergency surgery for fecal peritonitis, and the final study [25] analyzed only patients undergoing open appendectomy. The study sample size varied from 100 to 1185 patients; the role of laparoscopy was not clearly reported in the majority of studies.…”
Section: Clinical Resultsmentioning
confidence: 99%
See 2 more Smart Citations